Behaviors of particle size and bound proteins of oil bodies in soymilk processing. (1st March 2016) - Yan, Zunhao; Zhao, Luping; Kong, Xiangzhen; Hua, Yufei; Chen, Yeming
Highlights: Behaviors of oil bodies are explained from soybean to soymilk. Soybean proteins release from oil bodies with different rates by heating. Considerable soybean proteins are remained in oil bodies after heating. Heating induces the coalescence of oil bodies. Coalescence of oil bodies is impeded by phospholipids and residual proteins. Abstract: In unheated soymilk, extrinsic proteins are bound to intact oil bodies coated by one monolayer of phospholipids and oil body intrinsic oleosins. In this study, effects of heating (70–100 °C; 0–30 min) on particle size and bound proteins of oil bodies were examined in suspension (oil bodies from unheated soymilk into deionized water) and soymilk. Mass ratio of extrinsic proteins/oleosins of oil bodies in unheated suspension and soymilk was respectively 1.1 and 2.5. By heating, extrinsic proteins released from oil bodies with different rates, and Z-average size of oil bodies increased in the beginning; afterwards, residual extrinsic proteins (extrinsic proteins/oleosins: 0.31 in suspension and 0.74 in soymilk; 100 °C, 4 min) and Z-average size were affected little. The amount of residual proteins at 80–100 °C was negatively correlated with Z-average size of oil bodies in suspension ( R 2 = 0.996) and soymilk ( R 2 = 0.890).